Association between gestational weight gain, birth weight classification, and type of treatment in diabetic mothers - Baptistella do Nascimento, Iramar; Picinin Navarini, Guilherme; Ramos Vieira, Mariana; Ribeiro e Silva, Thiago; Fleig, Raquel; Silva, Jean Carl (O Mundo da Saúde, 2018)
The objective of the study was to identify the relationship between gestational weight gain, type of treatment used, and the weight of the baby at birth. This being an observational retrospective study, the primary outcomes evaluated were: the type of treatment used and the classification of the baby’s weight at birth. Collection occurred from January 2013 to May 2015. Multivariate multinomial logistic regression models were used to calculate odds ratios. Of the 682 pregnant women, 393 (57.6%) had a weight gain that was less than adequate, 140 (20.5%) showed adequate weight gain, and 149 (21.9%) had a weight gain that was higher than adequate. Weight gain that was less than adequate did not correlate with treatment used or with birth weight classification; higher-than-adequate weight gain was also not associated with the type of treatment used but decreased the chance of having a child considered normal for its gestational age by 50% and doubled the chance of having child considered large for gestational age. Comparing the groups according to the weight gain by means of the odds ratio, no difference was found in the therapy used.